(untitled) (Research, Society and Development, 2022)
Introduction: Gliomas are primary tumors of the central nervous system with an aggressive pattern of progression with a poor prognosis in terms of survival and quality of life. The current standard treatment consists of surgery with maximum excision associated with radiotherapy and chemotherapy, based mostly on the use of temozolomide. Since its introduction, the quality of life of patients undergoing this therapy has not been widely targeted and evaluated. Objective: To verify the quality of life of patients with glioblastoma after the introduction of temozolomide in the therapeutic protocols. Methods: A systematic literature review guided by the PICO and PRISMA protocol was conducted; PubMed, Medline and Lilacs databases were consulted. Results: Initially, 77 studies were found, after selection criteria, 35 articles were analyzed. No statistically significant change was found in overall quality of life in studies that analyzed temozolomide therapy versus different control therapies. Conclusion: The association of temozolomide with surgery and radiotherapy proved to be neutral, with no significant negative or positive impacts on the quality of life of patients with glioblastoma.